Pharmacogenetic and metabolite measurements are associated with clinical status in patients with rheumatoid arthritis treated with methotrexate: results of a multicentred cross sectional observational study. Issue 8 (27th January 2005) - Dervieux, T; Furst, D; Lein, D O; Capps, R; Smith, K; Caldwell, J; Kremer, J
Abstract : Objective: To investigate the contribution of red blood cell (RBC) methotrexate polyglutamates (MTX PGs), RBC folate polyglutamates (folate PGs), and a pharmacogenetic index to the clinical status of patients with rheumatoid arthritis treated with MTX. Methods: 226 adult patients treated with weekly MTX for more than 3 months were enrolled at three sites in a multicentred cross sectional observational study. Clinical status was assessed by the number of joint counts, physician's global assessment of disease activity, and a modified Health Assessment Questionnaire (mHAQ). RBC MTX PG and folate PG metabolite levels were measured by high performance liquid chromatography fluorometry and radioassay, respectively. A composite pharmacogenetic index comprising low penetrance genetic polymorphisms in reduced folate carrier (RFC-1 G80A), AICAR transformylase (ATIC C347G), and thymidylate synthase (TSER*2/*3) was calculated. Statistical analyses were by multivariate linear regression with clinical measures as dependent variables and metabolite levels and the pharmacogenetic index as independent variables after adjustment for other covariates. Results: Multivariate analysis showed that lower RBC MTX PG levels (median 40 nmol/l) and a lower pharmacogenetic index (median 2) were associated with a higher number of joint counts, higher disease activity, and higher mHAQ (p<0.09). Multivariate analysis also established that higher RBC folate PG levels (median 1062 nmol/l) were associated with a higher number of tender and swollen joints after adjustment for RBC MTX PG levels and the pharmacogenetic index (p<0.05). Conclusion: Pharmacogenetic and metabolite measurements may be useful in optimising MTX treatment. Prospective studies are warranted to investigate the predictive value of these markers for MTX efficacy.